(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Skeletal trauma refers to the damage inflicted to the bone, teeth or other human hard tissues. Human body, often, encounter traumatic insults at various stages before and after the death due to certain accidental or intentional acts of homicide or suicide or sometimes due to certain taphonomic factors. Beside establishing biological identity of unknown human remains, anthropologists are routinely involved in reconstruction of death scenes by understanding and interpreting the traumatic/taphonomic lesions imprinted to the recovered human remains. Each type of trauma imprints unique signatures as the mechanism of production of injuries is different with respect to force, angle, direction, tool used, morphology of bone etc. Traumatic injuries caused either during life time (ante-mortem) or just before the death (peri-mortem) can be related to events or circumstances surrounding death whereas post-mortem traumatic signatures may reflect the taphonomic damages or destructions of human remains. Trauma analysis is required to explain various facts like timing of trauma, cause and mechanism of trauma and circumstances around time of death and hence identification of the deceased. The information presented in this review article will provide proper understanding and ability to interpret the skeletal injuries for determining the mechanism and timing of bone trauma required in medicolegal death investigations. Traumatic injuries on the frontal bone, femurs and clavicles corroborated the heinous treatment of Ajnala victims before their death, the comprehensive trauma analysis was not possible due to badly damaged and fragmented nature of retrieved human remains consequent upon their non-scientific exhumation by some amateur archaeologists. Thus, safe and expert-mediated excavation of human remains found in forensic contexts becomes essential to reveal their traumatic history (if any) prior to death.